CONTINUITATEA ÎN ETAPELE DE FORMARE PROFESIONALĂ (Aspecte ale formării tânărului specialist chimist) - USM ADMIN (Moldova State University, 2011)
The article is dedicated to the problem of Education in Republic of Moldova, the development and implementation of curriculum in chemistry, the aspects of Professional Formation. There are reflected the objectives of Professional Orientation on the high school and superior stages. Special attention is paid to the concept of the Initial and Continuously Professional Formation, structure, functions and implementation modality of this formation in chemistry.